(untitled) (Journal for Studies in Humanities and Social Sciences, 2015)
Although regional and local government has been in existence in Namibia since the colonial times, it never existed in the communal areas of the territory. As a consequence of this, tribal authorities governed these parts of the territory. This underscored the importance of local government that time and also inhibited people from taking part in the decision making process on matters pertaining to their lives. This scenario reduced citizens to mere recipients of predetermined decisions of the colonial authorities. In some parts of the Police Zone, where regional and local government was practiced, local governments were mere extensions of the state in that all decisions were taken in colonial capitals and handed down to local governments for implementation. This effectively meant that regional and local government was subjected to central control, and also that, extensive centrally determined rules governed activities such as development planning and policy-making at sub national levels.